Efeitos da abolição da bradicardia reflexa nas respostas cardiorrespiratórias de tambaqui, Colossoma macropomum (Cuvier, 1818), em hipóxia severa: vagotomia versus inibição farmacológica - Sunti, Daniele Martinez de (Universidade Federal de São Carlos, 2013)
Hypoxic bradycardia is a reflex response to hypoxia observed in most fish species studied so far. This reflex is initiated by the stimulation of O2 chemoreceptors and induced by an increase in the inhibitory vagal tonus. Despite of being well described and characterized, the hypothesis that hypoxic bradycardia improves the O2 transference from the ventilatory water to the gills still remain to be proved. The utilization of different methods to inhibit hypoxic bradycardia (vagotomy and atropinization) may have contributed to generate different cardiorespiratory responses, making this issue even more controversial. In this study the cardiorespiratory variables (heart frequency fH, metabolic rate - VO2 , O2 extraction from the ventilatory current EO2, gill ventilation - VG , breathing frequency fR, and ventilatory requirement - VG / VO2 ) were measured in the tambaqui, Colossoma macropomum, under normoxia and after 40 min of exposure to severe hypoxia (20 mmHg) and the 3 subsequent hours of recovery. Each fish was subjected to this protocol before (Control group), after atropine administration (A group) and after vagotomy (V group). Under hypoxia the fish of control group displayed the characteristic hypoxic bradycardia (reduction of 56% in fH) with hyperventilation (increases of 96% in fR and 650% in VG ). This hyperventilation was probably responsible by the decrease in EO2 (65%) and, consequently, in the VO2 (62%), resulting in an increase of 1800% in the VG / VO2 . The beginning of the recovery period was characterized by an elevated VO2 (~200% above the normoxic values) accompanied by tachycardia (50.6 bpm) and gradual recovery of EO2, fR, VT and VG . Atropine and vagotomy elevated the fH in normoxia (from 32.0 ± 1.7 to 77.8 ± 4.1 and 80.6 ± 5.8 bpm), indicating a high basal vagal tone. In these two groups the fH remained constant during the experimental time course. This evidenced that the post-hypoxia tachycardia probably occurred as a consequence of a reduction in the cholinergic tonus. The groups control, atropinized and vagotomized did not show significant differences in EO2, VO2 and the other respiratory variables analyzed in any protocol. This results point out that hypoxic bradycardia does not improve the O2 transference to the gills, independently of the method employed to abolish the bradycardic reflex. Therefore, other hypotheses on the hypoxic bradycardia must be investigated in this species.
Keywords: Fisiologia comparada; Tambaqui (Peixe); Hipóxia; Bradicardia hipóxica; Vagotomia; Atropina; Hypoxia; Hypoxic bradycardia; Vagotomy; Atropine; CIENCIAS BIOLOGICAS::FISIOLOGIA